2021
DOI: 10.1002/pon.5861
|View full text |Cite
|
Sign up to set email alerts
|

Distress in hospitalized cancer patients: Associations with personality traits, clinical and psychosocial characteristics

Abstract: Objective To improve allocation of psychosocial care and to provide patient‐oriented support offers, identification of determinants of elevated distress is needed. So far, there is a lack of evidence investigating the interplay between individual disposition and current clinical and psychosocial determinants of distress in the inpatient setting. Methods In this cross‐sectional study, we investigated 879 inpatients with different cancer sites treated in a German Comprehensive Cancer Center. Assessment of determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The association between physical and psychological symptoms has been reported previously and is well-established. For example, a study among cancer in-patients showed that a worse physical condition is associated with higher distress (Pichler et al, 2022b). Another study by Leonhart et al (2017) revealed that higher somatic symptom severity is associated with higher levels of depression and anxiety as well as threatening and negative illness perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…The association between physical and psychological symptoms has been reported previously and is well-established. For example, a study among cancer in-patients showed that a worse physical condition is associated with higher distress (Pichler et al, 2022b). Another study by Leonhart et al (2017) revealed that higher somatic symptom severity is associated with higher levels of depression and anxiety as well as threatening and negative illness perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning clinical variables, greater distress has been associated with higher severity and more advanced stages of the disease in some studies [12,34,[40][41][42][43][44][45], but no relationship between such variables has been found in other investigations [37,46]. Patients with no evidence of disease were less likely to report high distress compared to patients with newly diagnosed cancer or in active treatment, in the study of Liu and colleagues [47].…”
Section: Introductionmentioning
confidence: 95%
“…Namely, patients diagnosed with digestive system malignancies, breast and genitourinary cancers, hematologic, lung and head and neck malignancies, as well as patients receiving chemo or radiotherapy, were found to have higher rates of clinical distress [12,48,49]. Again, these results were not consistently found, and the same occurs with time since diagnosis, which has not always been correlated with distress or psychological adjustment [37,45,50,51]. Methodological issues such as different sample sizes, tumour location, cancer stages, measures used to assess distress and different procedures may explain these inconsistencies.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the moment when the patient is given the diagnosis and told about the treatment they are going to receive constitutes a di cult process for the individual concerned and triggers a whole series of psychological consequences. Cancer patients are more likely than the general population to suffer from mental health issues, the posttraumatic stress disorder (PTSD), anxiety, depression, the risk of suicide, vulnerability, sleep and eating disorders, di culties in concentrating, and a temporal hiatus in their ability to lead their everyday lives [3][4][5][6] . These circumstances mean that the treatment of this disease needs to be biopsychosocial.…”
Section: Introductionmentioning
confidence: 99%